Metropolitan Cities supporting local adaptation processes. The case of the Metropolitan City of Venice - Magni, Filippo; Litt, Giovanni; Carraretto, Giovanni (TeMA - Journal of Land Use, Mobility and Environment, 2021)
Cities have a fundamental role in the adaptation and mitigation process to climate change. Even though cities will be the main subject of climate change impacts, they can propose solutions and build alternative scenarios. The difficulties that municipalities may encounter in their adaptation processes concern the lack of planning skills, technical knowledge, and human resources. To face these challenges Italian Metropolitan Cities can play a fundamental role in helping municipalities to plan and coordinate their efforts. The process in the Venetian territory has lasted many years and it has led to the awareness that local adaptation policies need to be addressed with broader support. The Metropolitan City of Venice has constructed a methodology for the planning of climatic adaptation. This methodology has been developed thanks to various plans and projects. These projects acted to increase the coordination between bodies, to define a broad area vision, to help municipalities to implement local actions. The role played by CMVe intends to direct public policies towards adaptation and mitigation in a structural way and with broad area governance. The process activated could be replicable in other Italian Metropolitan Cities in the approach and the result even if adapted to local needs.